Are Limb-sparing Surgical Resections Comparable to Amputation for Patients With Pelvic Chondrosarcoma? A Case-control, Propensity Score-matched Analysis of the National Cancer Database. Issue 3 (March 2019) - Kim, Chang-Yeon; Collier, Christopher D.; Liu, Raymond W.; Getty, Patrick J.
Abstract: Background: Chondrosarcoma is the second most frequent primary sarcoma of bone and frequently occurs in the pelvis. Surgical resection is the primary treatment with the two main operative modalities being limb-sparing resection and amputation. Contemporary management has trended toward limb-sparing procedures; however, whether this approach has an adverse effect on long-term survival is unclear. Questions/purposes: (1) What are the 5- and 10-year survival rates after limb-sparing surgery and amputation? (2) What factors are associated with survival after contemporary surgical management of pelvic chondrosarcoma? Methods: The 2004-2014 National Cancer Database, a nationwide registry that includes approximately 70% of all new cancers in the United States with requirement for 90% followup, was reviewed for patients diagnosed with pelvic chondrosarcoma who had undergone limb-sparing surgery or amputation. To compare survival, patient demographics, tumor attributes, and treatment characteristics were used to generate one-to-one propensity score-matched cohorts. Other factors associated with survival were determined through multivariable Cox regression. Three hundred eighty-five patients (75%) underwent limb-sparing surgery and 131 (25%) underwent amputation. Propensity score matching resulted in two balanced cohorts of 131 patients. Results: With the numbers available, we could not demonstrate a difference in overall survival between limb-sparing procedures and amputation. The 5-year survivorship was 70% (95% confidence interval [CI], 62%-79%) for limb-sparing surgery versus 70% (95% CI, 62%-79%) for amputation. The 10-year survivorship was 60% (95% CI, 48%-75%) for limb-sparing surgery versus 59% (95% CI, 48%-72%) for amputation. Kaplan-Meier survival analysis did not demonstrate a difference in survival (p = 0.9). Older age (hazard ratio [HR] = 1.029, p < 0.001), higher Charlson/Deyo comorbidity score (HR = 3.039, p = 0.004), higher grade (HR = 2.547, p = 0.005 for Grade 2; HR = 7.269, p < 0.001 for Grade 3; HR = 10.36, p < 0.001 for Grade 4), and positive surgical margins (HR = 1.61, p = 0.039) were associated with decreased survival. Conclusions: Our findings support the trend toward increased use of limb-sparing surgery for patients with pelvic chondrosarcoma. Orthopaedic oncologists may use our results when counseling their patients regarding treatment options. However, the choice of limb-sparing surgery versus amputation for these challenging patients should still be a highly individualized decision with careful discussion between the patient and the surgeon. Level of Evidence: Level III, therapeutic study.